Protein Phosphorylation and Mineral Binding Affect the Secondary Structure of the Leucine-Rich Amelogenin Peptide - Yamazaki, Hajime; Beniash, Elia; Yamakoshi, Yasuo; Simmer, James P.; Margolis, Henry C. (Frontiers in Physiology, 2017)
Previously, we have shown that serine-16 phosphorylation in native full-length porcine amelogenin (P173) and the Leucine-Rich Amelogenin Peptide (LRAP(+P)), an alternative amelogenin splice product, affects protein assembly and mineralization in vitro. Notably, P173 and LRAP(+P) stabilize amorphous calcium phosphate (ACP) and inhibit hydroxyapatite (HA) formation, while non-phosphorylated counterparts (rP172, LRAP(-P)) guide the growth of ordered bundles of HA crystals. Based on these findings, we hypothesize that the phosphorylation of full-length amelogenin and LRAP induces conformational changes that critically affect its capacity to interact with forming calcium phosphate mineral phases. To test this hypothesis, we have utilized Fourier transform infrared spectroscopy (FTIR) to determine the secondary structure of LRAP(-P) and LRAP(+P) in the absence/presence of calcium and selected mineral phases relevant to amelogenesis; i.e., hydroxyapatite (HA: an enamel crystal prototype) and amorphous calcium phosphate (ACP: an enamel crystal precursor phase). Aqueous solutions of LRAP(-P) or LRAP(+P) were prepared with or without 7.5 mM of CaCl2 at pH 7.4. FTIR spectra of each solution were obtained using attenuated total reflectance, and amide-I peaks were analyzed to provide secondary structure information. Secondary structures of LRAP(+P) and LRAP(-P) were similarly assessed following incubation with suspensions of HA and pyrophosphate-stabilized ACP. Amide I spectra of LRAP(-P) and LRAP(+P) were found to be distinct from each other in all cases. Spectra analyses showed that LRAP(-P) is comprised mostly of random coil and β-sheet, while LRAP(+P) exhibits more β-sheet and α-helix with little random coil. With added Ca, the random coil content increased in LRAP(-P), while LRAP(+P) exhibited a decrease in α-helix components. Incubation of LRAP(-P) with HA or ACP resulted in comparable increases in β-sheet structure. Notably, however, LRAP(+P) secondary structure was more affected by ACP, primarily showing an increase in β-sheet structure, compared to that observed with added HA. These collective findings indicate that phosphorylation induces unique secondary structural changes that may enhance the functional capacity of native phosphorylated amelogenins like LRAP to stabilize an ACP precursor phase during early stages of enamel mineral formation.